Treatment Strategies in Childhood Craniopharyngioma - Puget, Stéphanie (Frontiers Research Foundation, 2012)
The surgical management of craniopharyngiomas in children remains one of the more controversial topics in pediatric neurosurgery. Theoretically, the benign histology implies that total surgical excision would be sufficient to provide a cure. It has been widely established however, that in certain cases total excision may lead to unacceptable hypothalamic injury. The therapeutic goals for pediatric craniopharyngiomas therefore, require not just cure of the disease but also preservation of function. Over the last 15 years, there has been a growing worldwide advocacy for less extensive resection and for the utilization of multimodality therapy to limit morbidity. With this in mind, risk-adapted strategies designed to preserve hypothalamic structures have been developed. The preliminary results of these strategies appear to be encouraging. However, the long-term clinical outcome in terms of post irradiation complications and management of relapses is currently unknown.